2023
DOI: 10.1088/1748-9326/acc9d5
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment of spatiotemporal changes of frequency of terrestrial wind speed

Abstract: Wind energy, an important component of clean energy, is highly dictated by the disposable wind speed within the working regime of wind turbines (typically between 3 - 25 m s-1 at the hub height). Following a continuous reduction (“stilling”) of global annual mean surface wind speed (SWS) since the 1960s, recently, researchers have reported a “reversal” since 2011. However, little attention has been paid to the evolution of the effective wind speed for wind turbines. Since wind speed at hub height increases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This study highlights that irrigation may be a nonnegligible factor influencing global stilling. Previous studies have demonstrated that the global wind speed reduction, known as the "global stilling," has been a commonly accepted and ongoing phenomenon at the global and regional scales since the 1980s (Wu et al, 2018;Yang et al, 2021a;Zeng et al, 2019;Zhao et al, 2023). The global stilling can be mainly caused by the weakened pressure-gradient force (Lin et al, 2013), the large-scale atmospheric circulation anomaly (such as the North Atlantic Oscillation) (Minola et al, 2023), anthropogenic aerosols (Bichet et al, 2012), land use and cover changes (such as urbanization) (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights that irrigation may be a nonnegligible factor influencing global stilling. Previous studies have demonstrated that the global wind speed reduction, known as the "global stilling," has been a commonly accepted and ongoing phenomenon at the global and regional scales since the 1980s (Wu et al, 2018;Yang et al, 2021a;Zeng et al, 2019;Zhao et al, 2023). The global stilling can be mainly caused by the weakened pressure-gradient force (Lin et al, 2013), the large-scale atmospheric circulation anomaly (such as the North Atlantic Oscillation) (Minola et al, 2023), anthropogenic aerosols (Bichet et al, 2012), land use and cover changes (such as urbanization) (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was discovered here for the first time that there have been instances of sustained negative wind anomalies in the area, including those that corresponded to the years 2000-2010. Although the seasonal characteristics of the long-term trends of wind speed have been pointed out in [39], and its effects on wind power potential were briefly discussed in [40], only terrestrial winds were considered.…”
Section: Long-term Assessment Of Wind Energy Resourcesmentioning
confidence: 99%
“…The global decreasing trend was determined by those in Europe (−19%), South America (−16%), Australia (−14%) and Asia (−13%), while in North America an increasing trend (+3%) was found. The effects of this trend on terrestrial wind power potential and its association with wind frequency changes were briefly discussed in [40]. Based on the power wind curve of a specific turbine, it was estimated that wind energy had a continuous decline at a rate of 10.2 TW/year during 1981-2010, followed by a reversal, with a rate of 2.65 TW/year during 2011-2021.…”
Section: Introductionmentioning
confidence: 99%